2022
DOI: 10.3389/fcimb.2022.882661
|View full text |Cite
|
Sign up to set email alerts
|

Sera Metabolomics Characterization of Patients at Different Stages in Wuhan Identifies Critical Biomarkers of COVID-19

Abstract: We have witnessed the 2-year-long global rampage of COVID-19 caused by the wide spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, knowledge about biomarkers of the entire COVID-19 process is limited. Identification of the systemic features of COVID-19 will lead to critical biomarkers and therapeutic targets for early intervention and clinical disease course prediction. Here, we performed a comprehensive analysis of clinical measurements and serum metabolomics in 199 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
3
9
0
Order By: Relevance
“…Metabolomics techniques involve the identification and characterization of small molecules; the commonly used analytical techniques include nuclear magnetic resonance (NMR), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) ( 21 ). Non-targeted metabolomics studies analyze endogenous small molecule metabolites in the body without bias, providing information on thousands of compounds detected in samples and discovering the correlation between metabolites and physiological and pathological changes ( 22 ). Because each individual’s metabolic profile is unique, fluctuations and differences in metabolite levels directly reflect the mechanisms underlying disease development and progression ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics techniques involve the identification and characterization of small molecules; the commonly used analytical techniques include nuclear magnetic resonance (NMR), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) ( 21 ). Non-targeted metabolomics studies analyze endogenous small molecule metabolites in the body without bias, providing information on thousands of compounds detected in samples and discovering the correlation between metabolites and physiological and pathological changes ( 22 ). Because each individual’s metabolic profile is unique, fluctuations and differences in metabolite levels directly reflect the mechanisms underlying disease development and progression ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed description on LC-MS/MS analysis can be found elsewhere. 29 In brief, LC-MS/MS analyses were performed using an UHPLC system (Vanquish; Thermo Fisher Scientific) with a UPLC BEH Amide column ( , ) coupled to a Q Exactive HF-X (QE HFX) mass spectrometer (Orbitrap MS; Thermo). The QE HFX mass spectrometer was used owing to its ability to acquire MS/MS spectra in information-dependent acquisition mode in the control of the acquisition software (Xcalibur; Thermo).…”
Section: Methodsmentioning
confidence: 99%
“…Untargeted metabolomics revealed that lipids including PC (30:2) and PC (30:1) as biomarkers of prognosis play a key role in discriminating early hepatocellular carcinoma and compensated cirrhosis [78]. Lactate was identified as an essential molecule and reinforced Treg cells in the tumor microenvironment via lactylation [79]. The circulating level of gut microbe-generated metabolite trimethylamine N-oxide (TMAO) was associated with the risks of various cardiovascular diseases and can be used as a mediator biomarker for monitoring the severity and prognosis of atherosclerotic vascular disease [80].…”
Section: Disease Prognosis Analysis Via Mass Spectrometry-based Metab...mentioning
confidence: 99%